Improving Light Outcoupling and Addressing Measurement Specifics in Perovskite Light‐Emitting Diodes with Light Management Foils - Milan Kovačič; Marko Jošt; Janez Krč; Marko Topič (Advanced Photonics Research, 2025)
Near‐infrared perovskite light‐emitting diodes (PeLEDs), with four perovskite (PK) layer thicknesses and optional micro‐textured light management (LM) foil, are fabricated to evaluate their effects on light outcoupling efficiency. Devices with a 70 nm thick PK exhibit highest external quantum efficiencies (EQE), compared to those with thinner or thicker PK layers. The PK thickness influences the overall thin‐film stack and, consequently, the light outcoupling. LM foils significantly improve light outcoupling across all devices, with the thickest PK layer (160 nm) benefiting the most (60% increase), while the thinnest (40 nm) sees the least improvement (30%). Measured trends align well with optical modeling results, further highlighting the impact of sample holder design and pixel position on results. Theoretical optimization of PK thickness indicates unique optimal values for devices with or without LM foils. For devices incorporating LM foils, simulations predict an optimal PK thickness of 80 nm and an EQE of 27%. In contrast, for devices without LM foils, the optimal PK thickness of 60 nm corresponds to simulated EQE of 17%. In all cases, LM foils significantly enhance light outcoupling from bottom‐emitting PeLEDs while emphasizing the necessity to include LM foils in the thin‐film layer stack optimization process.